Catechesis of Seniors in the Context of Their Activity - Skoczylas, Kazimierz (Studia Warmińskie, 2020)
Modern seniors who are characterized by good health at the end of their professional activity engage in new forms of activity. Some of them are involved in the activities of universities of the third age, belong to the Family of Radio Maryja, are volunteers or use various forms of religious tourism and pilgrimages. Many manifestations of their activity come from the religiosity of seniors. The growing religiosity of seniors requires a systematic catechesis that helps them in its development. The church emphasizes that this catechesis should be adapted to the situation of a senior. Catechesis helps to read the religious meaning of this stage of life and to strengthen the motivation for Christian presence in the family and environment. Therefore, this catechesis should strengthen religious interest in faith, shape and sustain the motivation of Christian activity, in the Church and in the world. This is reflected in the Christian involvement in family upbringing, in the ecclesial community, for the social good and also in an attractive way of spending free time.